Quality-assured treatment in certified cancer center networks in upper Franconia, Germany: a population-centered retrospective cohort analysis based on data of the Bavarian cancer registry - Martin Emmert; Ingrid Gorodiscan; Andrea Thater; Doris Buchner; Alexander Kiani; Jacqueline Müller-Nordhorn; Stefan Rohrbacher (BMC, 2024)
Abstract Background Cancer is the second most common cause of death in Germany, and treatment in certified cancer networks is recommended to ensure high-quality care. This study sought to (1) determine the percentage of all primary tumors that might potentially have been treated in certified cancer networks and (2) assess the development and current state of quality-assured cancer care for all cancer patients from a locally defined region in Upper Franconia, Germany. Methods This study was a population-centered retrospective cohort analysis based on data from the Bavarian Cancer Registry (2017-2023). First, we determined all potentially available cancer network certifications and calculated the percentage of cancer care that could potentially have been conducted in certified cancer networks. Second, we considered the certification status of the involved healthcare providers and analyzed whether or not cancer care was actually carried out in certified cancer networks. Results Overall, 90.1% (62,119/68,973) of all primary tumors, from a total of 63,372 patients, might potentially have been treated in certified cancer networks. The percentage of patients actually receiving care in certified cancer center networks was 40.7% for initial diagnosis, 59.0% for surgery, 53.2% for chemotherapy, and 50.7% for radiotherapy; the weighted mean was 50.3%. The results thus ranged between 46.9% (2023) and 52.8% (2022). The highest proportions of patients who received quality-assured treatment in certified cancer center networks were determined for breast cancer (79.5%), colon cancer (73.1%), and lymphoma (60.1%); in contrast, the lowest results were shown for lung cancer (2.7%), anal cancer (0.0%), and mesothelioma (0.0%). Female patients as well as younger patients were significantly more likely to receive care in certified care networks compared with their counterparts. In addition, we did not find a clear trend whether patients in different tumor stages were more or less likely to receive care in certified care networks. Conclusions We found meaningful differences in the proportion of patients who received quality-assured treatment in certified cancer center networks. Following this, patients should receive comprehensive information about receiving care in certified cancer center networks and consider longer travel distances, especially for those cancer types without locally available certified cancer networks.